2009
DOI: 10.1111/j.1743-6109.2009.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Status in Patients with Erectile Dysfunction

Abstract: Introduction. Erectile dysfunction (ED) is increasingly recognized as a public health problem. The interaction between nitric oxide and reactive oxygen species is one of the important mechanisms implicated in the pathophysiological process of ED. Plasma contains various antioxidant components to prevent free-radical injury. Aim. The aim of this study was to determine and compare the oxidative and antioxidant status of peripheral venous blood in patients with ED of arteriogenic and non-arteriogenic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…First of all, both the evaluation of plasma hydroperoxides and Lag-time (Figure 1) confirm previous observations showing that the condition of oxidative stress in ED patients [26] overlaps the well-known OS status in patients with other pathologies [40]. Regarding peroxidation parameters, an intriguing point is the observation that in ED subjects RBC membrane fluidity shows no significant differences between patients and controls (Figure 2).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…First of all, both the evaluation of plasma hydroperoxides and Lag-time (Figure 1) confirm previous observations showing that the condition of oxidative stress in ED patients [26] overlaps the well-known OS status in patients with other pathologies [40]. Regarding peroxidation parameters, an intriguing point is the observation that in ED subjects RBC membrane fluidity shows no significant differences between patients and controls (Figure 2).…”
Section: Discussionsupporting
confidence: 84%
“…No ethics approval was required because no additional blood was needed for this study and this was explained thoroughly to all patients. This procedure has been accepted by several journals [26]. …”
Section: Methodsmentioning
confidence: 99%
“…One cause could be a reduced activity of DDHA, highly expressed in the liver (Nijveldt et al ., 2003), whose activity may be inhibited by a large series of traditional (hypercholesterolaemia, diabetes, smoking), non‐traditional (hyperhomocysteinaemia, inflammation, oestrogen deficiency, insulin resistence, hypothyroidism) risk factors and finally by oxidative stress. A fairly recent study showed that plasma reactive oxygen metabolite (ROS) concentrations were higher and plasma total antioxidant status (TAS) was lower in ED AR patients in comparison with ED NON‐AR patients and in controls (Barassi et al ., 2009). Furthermore, through uncoupling of NOS, increased production of superoxide could further impair DDAH, leading to a perpetuating increase in ADMA concentration (Sydow et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…2005), and the peak systolic velocity (PSV) and end‐diastolic velocity (EDV) were recorded at 5, 10, 15, 20 and 25 min after the injection in the proximal portion of the penis. Patients were classified as ‘non‐arteriogenic’ when their PSV was ≥35 cm/sec, or ≤35 cm/sec, but >25 cm/sec with concomitant EDV ≤ 0 cm/sec, and ‘arteriogenic’ when their PSV was ≤20 cm/sec (Barassi A et al ., 2009; Barassi et al ., 2010). The erection quality was estimated 20 min after each injection.…”
Section: Methodsmentioning
confidence: 99%
“…29,30 Increased production of reactive oxygen species (such as superoxide and peroxynitrite) in subjects with cardiovascular risk factors decrease bioavailability of NO and may lead to ED. 31 The study by Barassi et al 32 found that while the concentration of plasma reactive oxygen metabolite was higher in arteriogenic ED compared with non-arteriogenic ED, plasma total antioxidant level was lower in arteriogenic ED. In the study by Sezen et al, 33 serum total oxidant level and oxidative stress index were increased, and total antioxidant level was lower in the CAE group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%